Dietary fatty acid composition affects the apparent digestibility of algal carotenoids in diets for Atlantic salmon, Salmo salar. (27th January 2022) - Courtot, Emily; Musson, Dean; Stratford, Chris; Blyth, David; Bourne, Nicholas A.; Rombenso, Artur N.; Simon, Cedric J.; Wu, Xugan; M. Wade, Nicholas
Abstract: Astaxanthin (Axn) is the most commonly used carotenoid to enhance the flesh colouration of salmonids, which is one of the key criteria perceived to reflect the freshness and nutritional quality of the product and consequently affecting its price. However, the digestibility of astaxanthin by salmonids is highly variable, ranging between 20% and 60%. Axn digestibility can also be affected by total dietary lipid content and fatty acid (FA) composition (saturated FAs [SFA], mono‐unsaturated FAs [MUFA] or poly‐unsaturated FAs [PUFA]). This experiment contained four diets fed to juvenile Atlantic salmon for 2 weeks. Two diets formulated with either synthetic or algal carotenoids combined with poultry oil and two additional diets containing algal carotenoids with either tallow or canola oil. The aim of this study was to compare the feed intake, as a measure of diet palatability, and apparent digestibility (AD) of Axn between the two diets containing either synthetic or algal carotenoids. Results showed that algal carotenoids had significantly higher AD than synthetic Axn and that high levels of SFA, such as those in tallow, may inhibit the AD of algal carotenoids. Meanwhile, the high levels of MUFA and, in particular 18:1n‐9, in canola oil significantly improved the AD of algal carotenoids for Atlantic salmon. This study demonstrates the utility of algal carotenoids as natural pigment alternatives for farmed salmon, particularly beneficial when combined with different oil sources that contain more 18:1n‐9, such as in canola, and less SFA, such as in tallow, in order to optimize the utilization of dietary carotenoids.